2021
DOI: 10.2147/cmar.s308833
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Biliary Drainage Strategies for Patients with Malignant Hilar Biliary Strictures

Abstract: Purpose The main aim of this study was to compare the efficacy and safety of different biliary drainage strategies, including percutaneous transhepatic biliary drainage (PTBD) versus endoscopic biliary stenting (EBS) and unilateral versus bilateral stenting, in patients with unresectable malignant hilar biliary strictures (MHBSs). Patients and Methods This was a retrospective review of patients with inoperable MHBSs who underwent biliary drainage by either EBS or PTBD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…However, the patients evaluated were younger and a broad range of tumor entities causing MHO such as hepatocellular carcinoma, gallbladder cancer and metastases of distant primary tumors were included. Similarly, Liang et al reported CS rates (in this case TSB decrease > 75%) of 50.6% for unilateral and 69.6% for bilateral drainage (EBD or PTBD) in Chinese palliative patients with MHO compared to 29.2% in our cohort [14]. Again, patients were younger and tumor entities other than CCA were included.…”
Section: Discussionsupporting
confidence: 65%
“…However, the patients evaluated were younger and a broad range of tumor entities causing MHO such as hepatocellular carcinoma, gallbladder cancer and metastases of distant primary tumors were included. Similarly, Liang et al reported CS rates (in this case TSB decrease > 75%) of 50.6% for unilateral and 69.6% for bilateral drainage (EBD or PTBD) in Chinese palliative patients with MHO compared to 29.2% in our cohort [14]. Again, patients were younger and tumor entities other than CCA were included.…”
Section: Discussionsupporting
confidence: 65%
“…Technical success was defined as the successful deployment of the inserted stent across the site of the obstruction [15]. Clinical success was defined as a reduction in total bilirubin level to < 75% of the baseline level prior to treatment within a 1-month follow-up period [14]. Major complications associated with stenting included haemorrhage, cholangitis, and pancreatitis.…”
Section: Definitionsmentioning
confidence: 99%
“…The initial literature search retrieved 650 articles, of which 11 were ultimately included in the final meta-analysis (Figure 1), including one RCT [11] and 10 retrospective studies [12][13][14][15][16][17][18][19][20][21]. Figure 2 depicts the risk of bias results for this RCT, while all 10 retrospective studies exhibited NOS scores ranging from 6 to 8.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations